Differential responses of fast- and slow-conducting pyramidal tract neurons to changing accuracy demands during locomotion - Stout, E. E.; Beloozerova, I. N. (The Journal of Physiology, 2013)
Most movements need to be accurate. The neuronal mechanisms controlling accuracy during movements are poorly understood. In this study we compare the activity of fast- and slow-conducting pyramidal tract neurons (PTNs) of the motor cortex in cats as they walk over both a flat surface, a task that does not require accurate stepping and can be accomplished without the motor cortex, as well as along a horizontal ladder, a task that requires accuracy and the activity of the motor cortex to be successful. Fast- and slow-conducting PTNs are known to have distinct biophysical properties as well as different afferent and efferent connections. We found that while the activity of all PTNs changes substantially upon transition from simple locomotion to accurate stepping on the ladder, slow-conducting PTNs respond in a much more concerted manner than fast-conducting ones. As a group, slow-conducting PTNs increase discharge rate, especially during the late stance and early swing phases, decrease discharge variability, have a tendency to shift their preferred phase of the discharge into the swing phase, and almost always produce a single peak of activity per stride during ladder locomotion. In contrast, the fast-conducting PTNs do not display such concerted changes to their activity. In addition, upon transfer from simple locomotion to accurate stepping on the ladder slow-conducting PTNs more profoundly increase the magnitude of their stride-related frequency modulation compared with fast-conducting PTNs. We suggest that slow-conducting PTNs are involved in control of accuracy of locomotor movements to a greater degree than fast-conducting PTNs.